Gangguan Berbahasa Gagap pada Mustofa Tiktok dalam Konten Youtube BKK EP. 10 - Sabila Rahma Khoirun Nisa; Meilan Arsanti (MISTER: Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
Communication through language is a means of expressing intentions to other people. The speaker makes an effort to ensure that the listener or interlocutor understands and comprehends the intended message through the language used. A language disorder is a term used to characterize a condition in which a person has trouble comprehending or utilizing language. Stuttering is among the language impairments. The study is to examine Mustofa's language learning process with regard to BKK EP Youtube videos. 10. Mustofa has stuttered since he was a little child. An extensive investigation of the 10th episode of BKK Youtube material, which features Mustofa TikTok, is part of the research methodology used in this study. The study employs a descriptive qualitative methodology. The findings demonstrate that Mustofa has a stutter that is typified by frequent speech pauses in the middle of phrases, repeating of words, syllables, and letter sounds.